Eco-Theology: Islamic Ethics and Environmental Transformation in Islamic Boarding Schools - Maslani, Maslani (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Environmental problems, both on a national and global scale, are not merely technical issues but mostly come from human behavior. Environmental problems indicate moral problems; ways of human behavior in responding to the environment. Efforts to save the earth (environmental conservation) require changes in human behavior in interacting with the environment. This study aims to describe the environmental transformation in Bendakerep, Cirebon, through the application of ecotheology. Moral theory and liberation theology are used to approach environmental transformation. Based on the ethnographic method and the living religion approach, it can be described that ecotheology has been transformed in order to free society from environmental crises and humanitarian crises. The environmental transformation starts from community dialogue about the problems of their environmental life, intensive study of the text of the holy book (Al-Qur’an and Hadits) in Islamic Boarding School (pesantren) through the guidance of kyai to environmental conservation actions driven by pesantren for the benefit of society. Communities with environmental transformation are enlightened so that they can restore the local wisdom of their environment for the welfare of life